איך לפשט את n ^ 6 * (n ^ -2) ^ 5?

איך לפשט את n ^ 6 * (n ^ -2) ^ 5?
Anonim

תשובה:

# n ^ 6 * (n ^ -2) ^ 5 = 1 / n ^ 4 #

הסבר:

# n ^ 6 * (n ^ -2) ^ 5 #

לפשט # (n ^ -2) ^ 5 # על ידי החלת כלל המעריך # (a ^ m) ^ n = a ^ (m * n) #.

# n ^ 6 * n ^ (- 2 * 5) = #

# n ^ 6 * n ^ -10 #

פשט על ידי החלת כלל המעריך # a ^ m * a ^ n = a ^ (m + n) #.

# n ^ 6 * n ^ -10 = #

# n ^ (6 + -10) = #

# n ^ -4 #

החל את כלל המעריך #a ^ (- m) = 1 / a ^ m #.

# n ^ -4 = 1 / n ^ 4 #

תשובה:

# 1 / n ^ 4 #

הסבר:

# n = 6 * (n = (- 2 * 5)) = n ^ 6 * n ^ (- 10) = n ^ (6 + (- 10)) = n ^ (- 4) = 1 / n ^ 4 #